The association between renal resistive index and premature mortality after kidney transplantation is modified by pre-transplant diabetes status: a cohort study. Issue 9 (26th April 2019) - de Freminville, Jean-Baptiste; Vernier, Louis-Marie; Roumy, Jérome; Patat, Frédéric; Gatault, Philippe; Sautenet, Bénédicte; Bailly, Elodie; Chevallier, Eloi; Barbet, Christelle; Longuet, Hélène; Merieau, Elodie; Baron, Christophe; et al.
Abstract: Background: Renal resistive index (RI) predicts mortality in renal transplant recipients, but we do not know whether this is true in diabetic patients. The objective of this study was to analyse the long-term predictive value of RI for death with a functioning graft (DWFG) in renal transplant recipients with or without pre-transplant diabetes. Methods: We conducted a retrospective study in 1800 renal transplant recipients between 1985 and 2017 who were followed for up to 30 years (total observation period: 14 202 patient years). Donor and recipient characteristics at time of transplantation and at 3 months were reviewed. The long-term predictive value of RI for DWFG and the age–RI and arterial pressure–RI relationships were assessed. Results: A total of 284/1800 (15.7%) patients had diabetes mellitus before transplantation. RI was <0.75 in 1327/1800 patients (73.7%). High RI was associated with a higher risk of DWFG in non-diabetic patients [hazard ratio (HR) = 3.39, 95% confidence interval 2.50–4.61; P < 0.001], but not in patients with pre-transplant diabetes (HR = 1.25, 0.70–2.19; P = 0.39), even after multiple adjustments. There was no interaction between diabetes and age. In contrast, there was an interaction between RI and pulse pressure. Conclusion: Our study indicates that RI is not a predictor of DWFG in diabetic renal transplant recipients, in contrast to non-diabetic recipients. These findings could be due to a different age–RI or pulse pressure–RI relationship.